eval_UASI PENGGUNAAN ANTIBIOTIK DENGAN METODE GYSSENS PADA PASIEN DEMAM TIFOID DI INSTALASI RAWAT INAP RSUD HAJI MAKASSAR PERIODE JUNI-DESEMBER 2024 - Kakambong, Jessieca (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Typhoid fever is a common infectious disease in Indonesia, especially among productive age groups. The improper use of antibiotics in its treatment may lead to antibiotic resistance. This study aims to eval_uate the rational use of antibiotics in hospitalized typhoid fever patients at RSUD Haji Makassar using the Gyssens method. A descriptive observational study with a cross-sectional retrospective approach was conducted, using purposive sampling of 125 patient medical records from June to December 2024. Data were analyzed descriptively and statistically using Chi-square tests. Results showed that ceftriaxone was the most commonly used antibiotic (66%), followed by ciprofloxacin (22.8%). Rational use (category 0) was found in 59 cases (47.2%), while irrational use occurred in 66 cases (52.8%), predominantly in category III B (inappropriate duration). A significant association was found between gender and antibiotic rationality (p = 0.030), but no significant correlation was observed with age or length of stay. However, a highly significant correlation was found between the duration of antibiotic administration and rationality (p < 0.001). This study emphasizes the need for regular clinical audits and adherence to updated national treatment guidelines to prevent irrational antibiotic use and resistance.